1035325 Pengetahuan Remaja tentang Kehamilan Tidak Diinginkan di SMA Bakti Ibu 8 Palembang - Yuhemy Zurizah (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2019)
Abstract Lack of understanding of sexual behavior in adolescents will harm adolescents themselves, including their families. There are around 61% of adolescents aged 15-19 who have sexual relations and 74% of adolescents have sexual relations between the ages of 20-24 years, which encourages unwanted pregnancy. This study aims to determine the knowledge of adolescents about unwanted pregnancies at Bakti Ibu 8 Palembang High School. This type of research used in this research is descriptive research. This research is an observational research with cross sectional approach. The population in this study were all Bakti High School students as many as 270 students. The sample in this study amounted to 54 students. This research was conducted in August 2019 at Bakti Ibu 8 Palembang High School. Based on the results of this study concluded that the level of knowledge of respondents in terms of the age characteristics of the majority of respondents aged 16 years (42.6%). In terms of the sex characteristics of the respondents, the majority were women (68.5%). The level of knowledge of adolescents about unwanted pregnancy is included in both categories as much as 51.9% and the rest have a sufficient level of knowledge as much as 48.1%. Keywords: Teenagers, Unwanted Pregnancy, Adolescent Reproductive Health